2015
DOI: 10.1371/journal.pone.0138674
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Thermus aquaticus Y51MC23

Abstract: Thermus aquaticus Y51MC23 was isolated from a boiling spring in the Lower Geyser Basin of Yellowstone National Park. Remarkably, this T. aquaticus strain is able to grow anaerobically and produces multiple morphological forms. Y51MC23 is a Gram-negative, rod-shaped organism that grows well between 50°C and 80°C with maximum growth rate at 65°C to 70°C. Growth studies suggest that Y51MC23 primarily scavenges protein from the environment, supported by the high number of secreted and intracellular proteases and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Metabolism varies widely among thermophiles and general trends are hard to discern as it is extremely difficult to distinguish between the effect of speciation versus adjustment to extreme environments. For example, three main glycolytic pathways are used by bacteria in general: the traditional Embden-Meyerhof (EM) glycolysis, the Entner-Doudoroff pathway, and the pentose phosphate pathway; all three can also be found in different thermophilic bacteria (Counts et al 2017;Swarup et al 2014;Brumm et al 2015;Selig et al 1997) . In archaea, how ever, only modified variants of classical sugar degradation pathways were identified (Brasen et al 2014;Selig et al 1997) .…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism varies widely among thermophiles and general trends are hard to discern as it is extremely difficult to distinguish between the effect of speciation versus adjustment to extreme environments. For example, three main glycolytic pathways are used by bacteria in general: the traditional Embden-Meyerhof (EM) glycolysis, the Entner-Doudoroff pathway, and the pentose phosphate pathway; all three can also be found in different thermophilic bacteria (Counts et al 2017;Swarup et al 2014;Brumm et al 2015;Selig et al 1997) . In archaea, how ever, only modified variants of classical sugar degradation pathways were identified (Brasen et al 2014;Selig et al 1997) .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this include “rotund bodies” in Thermus aquaticus (Brumm P. J. et al, 2015), the outer membrane “toga” of Thermotoga maritima (Huber et al, 1986) and the multicellular spheres of D. turgidum (Svetlichny and Svetlichnaya, 1988). Regulation of these morphologies may be controlled by the action of SpoVS (Brumm P. J. et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Examples of this include “rotund bodies” in Thermus aquaticus (Brumm P. J. et al, 2015), the outer membrane “toga” of Thermotoga maritima (Huber et al, 1986) and the multicellular spheres of D. turgidum (Svetlichny and Svetlichnaya, 1988). Regulation of these morphologies may be controlled by the action of SpoVS (Brumm P. J. et al, 2015). D. turgidum possesses a gene coding for SpoVS (Rigden and Galperin, 2008) (Dtur_0800) similar to SpoVS proteins found in sporulating Firmicutes species as well as in the non-sporulating Thermus - Deinococcu s and Thermotoga groups, but not in non-sporulating Firmicutes species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also several other commercial available Mate Pair Library kits that have their own unique features. For example, the NxSeq Long Mate from Lucigen has shown that they could improve assembly quality [8]. Sage Science has improved the MP method using the SageELF, which lowers the needed sample input [9].…”
Section: Mate-pair Next Generation Sequencing (Mp-seq)mentioning
confidence: 99%